Public Spending and Income Inequality: Evidence from Indonesia - Nazah Lailatus Syarifah; Yozi Aulia Rahman (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
Income inequality represents a persistent structural challenge that poses a serious threat to inclusive economic development in Indonesia. This study investigates the impact of public expenditure on education, health, and social protection, GRDP per capita, and poverty on income inequality across 34 provinces in Indonesia during the 2015–2023 period. The analysis applies the System Generalized Method of Moments (Sys-GMM) to address dynamic panel characteristics and intertemporal persistence, allowing for consistent and reliable parameter estimation. The empirical findings indicate that lag income inequality, education expenditure, per capita GRDP, and poverty significantly contribute to higher income inequality. In contrast, public spending on health and social protection does not exhibit a statistically significant effect. Overall, the results suggest that fiscal policy, particularly public expenditure allocation, has not yet operated optimally as an instrument for reducing inequality, highlighting the importance of more targeted and equity-oriented fiscal interventions.